2010
DOI: 10.2478/s11756-010-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of heavy-metal resistant culturable bacteria and resistance determinants from a heavy-metal-contaminated site

Abstract: In this study we performed a phylogenetic analysis of a culturable bacterial community isolated from heavymetal-contaminated soil from southwest Slovakia using 16S rRNA (16S rDNA) and heavy-metal resistance genes. The soil sample contained high concentrations of nickel (2,109 mg/kg), cobalt (355 mg/kg) and zinc (177 mg/kg), smaller concentrations of iron (35.75 mg/kg) and copper (32.2 mg/kg), and a trace amount of cadmium (<0.25 mg/kg). A total of 100 isolates were grown on rich (Nutrient agar No. 2) or minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 37 publications
1
42
1
3
Order By: Relevance
“…Soil pollution with heavy metals leads to the appearance of heavy-metal resistant rhizobateria in the soil of industrial regions (Aleem et al 2003). Karelová et al (2011) performed a phylogenetic analysis of a culturable bacterial community isolated from heavy-metal contaminated soil from southwest Slovakia using 16S rDNA and heavy-metal resistance genes. Many studies have focused on the effects of heavy metals on bacterial community structure (Khan et al 2010;Karelová et al 2011), and relatively many bacteria have already been isolated from different heavymetal-contaminated environments.…”
Section: Characterization Of Soil and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Soil pollution with heavy metals leads to the appearance of heavy-metal resistant rhizobateria in the soil of industrial regions (Aleem et al 2003). Karelová et al (2011) performed a phylogenetic analysis of a culturable bacterial community isolated from heavy-metal contaminated soil from southwest Slovakia using 16S rDNA and heavy-metal resistance genes. Many studies have focused on the effects of heavy metals on bacterial community structure (Khan et al 2010;Karelová et al 2011), and relatively many bacteria have already been isolated from different heavymetal-contaminated environments.…”
Section: Characterization Of Soil and Watermentioning
confidence: 99%
“…The metal accumulating capacity of microorganisms can be exploited to remove, concentrate and recover metals from mine tailings and industrial effluents (Malekzadeh et al 2002). Several reports of aerobic bacteria accumulating metals like Ag, Co, Cd, Cu, Cr, and Ni (Mengoni 2001;Chovanová et al 2004;Adarsh et al 2007;Karelová et al 2011) are available. Microorganism-based remediation techniques, such as bioremediation, show potential for their ability to degrade and detoxify certain contaminants (Sherameti & Varma 2011).…”
Section: Introductionmentioning
confidence: 99%
“…But these have not been well elucidated for the majority of known actinobacteria and have only just recently started attracting scientists' interest. Karelova et al, (2011) defined the actinobacteria phylum as the second well represented group after proteobacteria (α, β and γ), in heavy metal contaminated farm land in southwest Slovakia, and furthermore, isolated nine new species and genera in the same study. Another study examining 16s rDNA and 16s rRNA in metal contaminated bulk and rhizosphere soils in the goal to compare diversity of existing and metabolically active populations in those sites, showed that the most predominant phylotypes in both sites belong to actinobacteria compared to α proteobacteria (Gremion et al, 2003).…”
Section: Actinobacteria and Metalsmentioning
confidence: 82%
“…These enable them to colonize hostile habitats, including soils contaminated with heavy metals and metalloids. In fact, biodiversity studies have shown the high abundance and ubiquity of actinobacteria in such soils, in addition to the most expanded clade of α Proteobacteria (Karelova et al, 2011). Furthermore, isolation works have shown that many strains can survive high metal concentration using panoply of mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation